Molecular dynamics studies of human β-Glucuronidase - Noorbatcha, Ibrahim Ali; Masrur Khan, Ayesha; Mohd. Salleh, Hamzah (Science Publications, 2010)
Problem statement: The enzyme β-glucuronidase is being used as a reporter molecule in the area of genetic engineering, as a component of prodrug therapy in cancer treatment and in the scouring process of cotton fabrics. However, a detailed understanding of the factors responsible for the stability and the activity of this enzyme is still not available. Molecular Dynamics (MD) simulations provide an estimate of equilibrium and dynamic properties of enzyme systems that cannot be calculated analytically. With this perspective, molecular dynamics simulations of human β- glucuronidase (GUS) have been carried out to determine the behavior of this enzyme in vacuum and solvent environments at a defined temperature.